ANALYSIS OF REGIONAL INEQUALITY IN SOUTHEAST SULAWESI - Dewangga, Puspa; Saenong, Zainuddin; Samrin, La Ode Muhammad Arfan (Journal Economics Technology And Entrepreneur, 2025)
This study aims to analyze regional development inequality in Southeast Sulawesi Province. The research objectives are to identify interregional inequality levels. The method employs quantitative descriptive analysis using the Williamson Index and per capita GRDP data from 2019-2023 from the Central Statistics Agency. The results reveal significant development inequalities between urban and rural areas, with rural regions lagging in infrastructure access and economic opportunities. The COVID-19 pandemic exacerbated these inequalities. The study concludes that integrated policies are needed to reduce gaps through infrastructure strengthening, economic diversification, and local needs-based development programs.